Heat and salt flow in subsea permafrost modelled with CryoGRID2. - Angelopoulos, Michael; Westermann, Sebastian; Overduin, Pier Paul; Faguet, Alexey; Olenchenko, Vladimir; Grosse, Guido; Grigoriev, Mikhail N (PANGAEA, 2018)
Two separate field excursions were carried out in 2017 to investigate subsea permafrost degradation offshore of the Bykovsky Peninsula in Siberia. In April, four ice cores were drilled offshore to measure sea ice thickness, snow thickness, and water depth. In July, multiple conductivity, temperature, and depths (CTD) sensors were deployed to measure seawater properties like temperature, salinity, and electrical conductivity. Furthermore, electrical resistivity surveys were taken perpendicular to and crossing the shoreline of the Bykovsky Peninsula to estimate the depth of ice-bearing permafrost.
Conductivity, temperature and depth (CTD), snow and ice thickess and apparent resisitivity on the Bykovsky Peninsula, Lena Delta, in April and July 2017
Keywords: AWI_PerDyn; Permafrost Research (Periglacial Dynamics) @ AWI; PETA-CARB; Rapid Permafrost Thaw in a Warming Arctic and Impacts on the Soil Organic Carbon Pool